Thermal and spectral impact of building integrated Mirrored Light Pipe to human circadian rhythms and thermal environment. Issue 5 (28th May 2022) - Malet-Damour, Bruno; Fakra, Damien Ali Hamada
ABSTRACT: Light holds an important place in the way of life of humans. The first type of lighting which could be exploited was daylight. Tubular Daylight Guidance Systems (TDGS) transport and distribute this daylight inside a building. This article focuses on one of the best known: the Mirrored Light Pipe. MLPs are multiple specular reflectance transporters. This paper presents (i) state of the art on thermal and spectral studies on light pipes from 1998 to 2021 and (ii) proposes an experimental analysis on MLP in the climatic environment with a high solar resource for different spectral bands of the daylight spectrum. The results show that the thermal impact of the light pipe is limited. Moreover, it is demonstrated that this device promotes natural circadian rhythms. A comparison with artificial lighting highlights this device as an ideal solution for bioclimatic building design. HIGHLIGHTS A short review on experimental and numerical thermal results on Mirrored Light Pipe (MLP) New experimental observations for the thermal aspect of MLP in high solar potential climate Evaluation of the MLP efficiency on human circadian rhythms.